Pelayanan Sosial Dalam Pelaksanaan Program Bimbingan Keterampilan Untuk Meningkatkan Kemandirian Anak Jalanan Di PSBR Taruna Jaya 2 - Arfan Fajri; Muhammad Sahrul (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The process of socializing self-reliance services for street children at PSBR Taruna Jaya 2 has several guidance activities such as social guidance which provides physical and mental guidance and skills guidance. This research was conducted at the Taruna Jaya 2 DKI Jakarta Youth Development Social Institution (PSBR Taruna Jaya 2) among street children who received skills guidance. The method used is qualitative with data collection techniques of observation, interviews and documentation. The informants interviewed were social workers, institutional managers, instructors and street children. The results of the research show that the condition of street children before receiving guidance at PSBR Taruna Jaya 2 did not have special skills to make a living, they were young men aged 18 to 30 years. They were caught in control operations by the authorities, living on the streets acting as street children (anjal), homeless people and beggars (gepeng), silver people, street singers, clown singers and punks. Education is low and some cannot read, write and count. Participated in coaching at PSBR Taruna Jaya 2 for 6 months. Implementation of skills guidance programs in the form of welding, car or motorbike repair, electronics, air conditioning and screen printing. The implementation of the program is funded by the Regional Government of DKI Jakarta and involves social workers, institutional managers, psychologists and instructors. Monitoring and evaluating training guidance with internships at collaborating companies. The independence of street children means that by terminating street children, they become aware of the law, return to their families and live in the community, some have even gotten jobs and opened their own businesses so they can cover their own needs without depending on other people.